Pengaruh Penerapan Green Accounting, Green Competitive Advantage, Capital Structure, dan Environmental Performance Terhadap Nilai Perusahaan Pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023 - Wahyu Ramadhan; Hermi Karom (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to examine the influence of Green Accounting, Green Competitive Advantage, Capital Structure, and Environmental Performance on Firm Value. The research was conducted on energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period, with a total of 111 observations. The analytical method employed was multiple linear regression. The results show that Green Competitive Advantage and Environmental Performance have a significant positive effect on Firm Value, while Green Accounting and Capital Structure have no significant effect. These findings reinforce the relevance of the Resource-Based View and Legitimacy Theory in explaining how firm value is created through sustainability strategies. On the other hand, the insignificant effect of Green Accounting is likely due to the limitations of using a dummy-based measurement, which does not fully capture the quality of implementation. The implications of this study highlight the strategic importance of environmental competitiveness and environmental performance as key determinants of firm value in the energy sector.